Investigation of Variables Affecting the Adsorption of Cadmium Ions in Aqueous Solution Using low-cost Adsorbents (Fly Ash) - Alburki , Salem M. (Sebha University Conference Proceedings, 2025)
This study investigated the effect of some variables on the removal of Cadmium ions from Aqueous solutions using materials produced by some factories and industrial units as an unused or limited-use by-product, such as fly ash. It was tested as an adsorbent for the removal of cadmium ions (Cd (II)). Some variables that directly affect the deionization process were studied, such as pH, required dose, initial metal concentration, contact time, and particle size. Through the experiments conducted and the results obtained, some removal percentages differed based on the studied variable, as the best dose was 3 grams and the best concentration was 300 parts per million, and the removal percentage reached 83%. The remaining prepared concentrations differed, as the best time was 100 minutes, with a particle size of 75 micrometers, and the best pH was 6. The removal percentage changed with temperature, as it was 81% at 25°C and increased to 89% at 55°C. The results showed that cadmium is highly adsorbed on fly ash and can be an economical method for removing cadmium from aqueous solutions..